Individual OCD-provoking stimuli activate disorder-related and self-related neuronal networks in fMRI. (30th January 2019) - Viol, Kathrin; Aas, Benjamin; Kastinger, Anna; Kronbichler, Martin; Schöller, Helmut; Reiter, Eva-Maria; Said-Yürekli, Sarah; Kronbichler, Lisa; Kravanja-Spannberger, Brigitte; Stöger-Schmidinger, Barbara; Aichhorn, Wolfgang; Schiepek, Günter
Highlights: Further evidence of superiority of individual stimuli for fMRI. Only the individual picture set showed significant neuronal activation after correction for false-positive results. Results correspond to enhanced scores in picture rating for the individual pictures. However, the overlap with the network of self-referential processing and memory retrieval was identified as confound when individual symptom-provoking stimuli only are used. Abstract: For patients with Obsessive-Compulsive Disorder (OCD), whose triggers are highly idiosyncratic, individual stimulus material has been used in several fMRI studies. This study aims at comparing individual to standardized picture sets and at investigating a possible overlap of the former with the self-referential neuronal network. During fMRI-scanning, 17 inpatients with OCD and 17 healthy controls were exposed to pictures of their personal triggers, photographed in their domestic environments, to standardized pictures designed to provoke OCD symptoms, and to neutral pictures. Whole-brain analyses were calculated and the pictures were rated by both patients and controls with respect to valence, arousal, and coping. Patients rated the individualized stimuli lower in valence and coping and higher in arousal compared to controls, and also compared to standardized OCD- and neutral stimuli. The individual stimuli elicited neuronal activity in the cingulate cortex, hippocampus, insula, middle frontal/precentral gyrus, superior/inferior parietal lobe, and precuneus, while no group difference was detected by the standardized OCD-stimuli. In conclusion, individual picture sets facilitate the detection of neuronal activity, but the results might be confounded due to the overlap with the network of self-referential processing and memory retrieval. The use of individual symptom-provoking and individual neutral stimuli would therefore be optimal.